2017
DOI: 10.3390/catal7030082
|View full text |Cite
|
Sign up to set email alerts
|

Biotemplated Mesoporous TiO2/SiO2 Composite Derived from Aquatic Plant Leaves for Efficient Dye Degradation

Abstract: Abstract:The biotemplating technique is an environmental-protective high-efficiency new technology by which the resulting TiO 2 may simultaneously attain the duplication of structure and self-doping elements from biotemplate materials, which is highly desirable for photocatalytic applications. In this paper, aquatic plant leaves-including reed, water hyacinth, and duckweed-were used as both templates and silicon precursors to successfully synthesize biomorphic TiO 2 /SiO 2 composite with mesoporous structures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The photocatalytic activity of TiO 2 /SiO 2 samples was compared to that obtained with P25 and non-templated TiO 2 under simulated sunlight irradiation. The results showed that the photocatalytic activity of samples prepared by biotemplating was higher than that obtained by the other photocatalysts (degradation yields of 72.0% and 61.4% of templated samples vs. 42.4% and 24.5% of P25 and TiO 2 particles prepared with no template, respectively), and that it depended on the type of plant [20].…”
Section: B) Decontamination Reactionsmentioning
confidence: 85%
See 1 more Smart Citation
“…The photocatalytic activity of TiO 2 /SiO 2 samples was compared to that obtained with P25 and non-templated TiO 2 under simulated sunlight irradiation. The results showed that the photocatalytic activity of samples prepared by biotemplating was higher than that obtained by the other photocatalysts (degradation yields of 72.0% and 61.4% of templated samples vs. 42.4% and 24.5% of P25 and TiO 2 particles prepared with no template, respectively), and that it depended on the type of plant [20].…”
Section: B) Decontamination Reactionsmentioning
confidence: 85%
“…Another virus that has been used as a pattern for biotemplating approaches is the M13 phage, as its genetically engineered mutants present modifications on the surface that bind to nanoparticles or nanotubes, improving the functionality of the material [17]. Wood [18], cotton [19], aquatic plants [20], green leaves [1,21], or even animal products [22] have also been used as templates. Butterfly wings are of great interest as they present an intricate and complex microstructure and photonic resonances that control their structural color and make them very suitable for catalysis and electrochemical applications [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…As an agricultural waste, it is estimated that more than 7.0 million tons of eggshell waste in the world were produced every year [23]. ESM is one of the most widely used natural biological templates, and its unique 3D network structure provides its natural advantages with low cost and non-toxicity as a supporting template [24], compared to other biological templates, such as bacterial virus templates [25], algae templates [26], plant templates [27], and DNA templates [28]. The main advantage of ESM is that it has a wide range of sources, low cost, no pollution to the environment, and simple separation and purification process [29].…”
Section: Introductionmentioning
confidence: 99%
“…The intimate contact can facilitate inter particle charge transfer from brookite to anatase and reduce the recombination of electron-hole pairs. Thirdly, the large surface area can provide more active sites and improve the diffusion and migration of MO in the process of photodegradation [36]. Furthermore, the competitive diffusion of the H 2 O and dye molecules, dye molecule structure, and photocatalytic degradation route are also the factors influencingthe photocatalytic process [37].…”
Section: Possible Reasons For the Enhancement Of The Visible-light Pementioning
confidence: 99%